Process-Oriented Measurement of Emotion Regulation: General and Specific Associations With Psychosocial Adjustment and Well-Being in (Pre-)Adolescence - Rueth, Jana-Elisa; Lohaus, Arnold (Frontiers in Psychiatry, 2022)
The development of emotion regulation (ER) is associated with children’s and adolescents’ psychosocial adjustment and well-being. In this regard, previous studies have examined the role of different ER strategies, which can be characterized as being functional (e.g., reappraisal, problem solving) or dysfunctional (e.g., suppression, rumination). Based on the process model of emotion regulation, the strategies can also be classified according to their temporal position within the emotion generative process, with five families of ER strategies being proposed: situation selection, situation modification, attentional deployment, cognitive change, and response modulation. This study aimed to examine the role of ER for adolescents’ psychosocial adjustment (internalizing and externalizing problems, prosocial behavior) and well-being. First, associations were investigated on a more general level by distinguishing between functional and dysfunctional ER. Second, relations were examined on a more specific level by additionally distinguishing between the five families of ER strategies as suggested in the process model of ER. Questionnaire self-reports of N = 1,727 German children and adolescents (55% girls) aged 9 to 18 years (M = 13.03, SD = 1.75) collected in schools were analyzed. Path analyses showed that more functional and less dysfunctional ER in general is associated with fewer internalizing and externalizing symptoms, and higher well-being. Prosocial behavior was only positively related to functional but not dysfunctional ER. Analyses of associations on the level of specific categories of ER strategies generally showed a similar pattern, but in part indicated differential associations with the dependent variables: Internalizing problems were particularly associated with functional situation selection, dysfunctional cognitive change and dysfunctional response modulation. Externalizing problems were associated with functional situation selection and response modulation, as well as numerous dysfunctional strategies, none of which were particularly salient. Similarly, numerous rather than single specific associations emerged between prosocial behavior and the five categories of functional ER strategies. Well-being was particularly associated with functional situation selection and dysfunctional cognitive change. Overall, a more precise assessment of ER, as implemented in this study, could not only advance research in this field, but can also be helpful in planning and evaluating prevention and intervention programs.